(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2021)
Samarium is currently used in many applications, such as catalysts, lasers and metal alloys. Samarium is also employed to absorb neutrons in nuclear reactors. In medicine, samarium is used in the form of radioactive 153Sm to produce radiopharmaceuticals. A simple process for the preparation of pure samarium acetate was studied. The raw material, which was used in the form of rare earth carbonates was produced industrially from the chemical treatment of Brazilian monazite. Ion exchange chromatography was performed using a strong cationic resin to fractionate rare earth elements (REE). Under these conditions, 99.9% pure Sm2O3 and yield greater than or equal 60% was eluted by ammonium salt of ethylenediaminetetraacetic acid (EDTA) solution in controlled pH. The EDTA-samarium complex was transformed into samarium oxide, which was subsequently dissolved in acetic acid to obtain the samarium acetate. Molecular absorption spectrophotometry was used to monitor the samarium and sector field inductively coupled plasma mass spectrometry was used to certify the purity of the samarium acetate. The solid salt was characterized by chemical analysis, thermal analysis, infrared spectroscopy and X ray diffraction. The analytical data collected allowed to conclude that stoichiometric formula for the samarium acetate obtained is Sm(CH3COO)3.4.H2O. Keywords: Samarium, Ion exchange, Rare Earth.